Expectations and beliefs of Mexican entrepreneurs, from a gender perspective - Pérez-Paredes, Alfredo (2021)
The objective of this research is to determine the characteristics that explain the motivation of Mexican entrepreneurs from various viewpoints: chances and needs, flexibility, profit, and their relation with gender and with domestic affairs. The data collection was by survey, with a 32-item instrument, on a sample of entrepreneurs from the municipalities of Puebla and Tlaxcala. The data treatment was carried out by means of multivariate logistic regression. The findings were that the Mexican women entrepreneurs’ motivation is mainly to cooperate with family needs and not to neglect family responsibilities because it is the institutional role assigned to the woman (mother). Another reason for their decision to start a business is that people earn less being waged workers; that is because they suffer from either cultural or social pressures, or they feel frustrated in their jobs. Besides, Mexican entrepreneurs prefer to use external financial sources before risking their owns, and above all, they are driven by expectations or beliefs about the costs-benefits they may obtain, and not necessarily by planned, prepared, or analyzed start-ups.